Pengaruh Perencanaan Pajak, Ukuran Perusahaan, Dan Return On Asset Terhadap Manajemen Laba (Studi Kasus Pada Perusahaan Subsektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2017-2020) - Anisya Fitri Sofyanti; Rusmianto Rusmianto; Maryani Maryani (Universitas Malahayati, 2022)
this study purpose to determine the effect of tax planning, firm size, and return on assets on earnings management. The population in this research is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020 with a total population of 28 companies. Sampling using the purposive sampling method, namely the selection of samples with certain criteria and obtained 13 companies that meet the criteria. The method of collecting data is through secondary data documentation in the form of annual reports of companies in the food and beverage sub-sector obtained from downloading financial reports published by www.idx.co.id. The analytical tool used is multiple linear regression with hypothesis testing, namely the F-test, T-test, and the coefficient of determination (R2) using the SPSS.V.22. Program. The results showed that partially and simultaneously Tax Planning, Firm Size, and Return On Assets had no effect on Earnings Management.Keyword : tax planning, firm size, return on asset, earning management